Comparison of biomarkers in retained oil and expelled oil of lacustrine marlstone determined by hydrous pyrolysis: Application to hydrocarbon migration determination in the tight oil reservoir. Issue 4 (27th December 2021) - Guo, Ruibo; Zhang, Jinchuan; Tang, Xuan; Jiang, Zaixing; Zhang, Bin
Abstract : Oil in an unconventional tight reservoir is considered to migrate from a very adjacent reservoir or be impregnated in situ within source rocks, but their large hydrocarbon molecular fractions during short‐distance migration in the tight system are poorly understood. In order to explore the evolution characteristics and differences of the geochemical properties, especially the biomarkers, between expelled oil (just detached from source rock and not undergoing long‐distance migration) and retained oil under different thermal evolution stages of lacustrine marlstone. Semi‐open hydrous pyrolysis was conducted on an immature lacustrine marlstone collected from the third member of the Eocene Shahejie Formation in Shulu Sag, Bohai Bay Basin and the hydrocarbon product expelled from and remained in the rock during pyrolysis were collected and analysed with gas chromatography–mass spectrum instrument. The results indicate that the saturates compositions show expelled oil having commonly lower thermal maturity than retained oil because expelled oil is a mixture of multiple‐term hydrocarbon expulsions, while retained oil is the remained final hydrocarbon product of pyrolysis in semi‐open experimental system. The hydrocarbon migration has a significant effect on the maturity‐related parameters distribution such as 20S/(20S + 20R) and αββ/(αββ + ααα) for C29 steranes. Hydrocarbon expulsion enables Ts/(Ts + Tm) ratio in expelled oil is much greater than that of retained oil at lower matural stage. The saturated hydrocarbon maturity biomarkers in retained oil and expelled oil vary in a subtly different pathways with increasing maturity, comparatively the aromatic hydrocarbon biomarkers, such as triaromatic steroids and methyl‐phenanthrene (MPI1 and MPI2 ), regularly changed during maturation, which is not obviously affected by migration effects and can be used not only for thermal maturity predications but also for oil–oil or oil–source correlation. C29 20S/(20S + 20R) and C29 αββ/(αββ + ααα) commonly are preferable maturity parameters for shale or mudstone, reflecting that mineral matrix and oil in source rock are not affected by migration and supposed to have an oil thermal maturity corresponding to depth. Combined with some tight reservoir cases in North America and China, the biomarker ratios variation along depth and its abnormal value can be used to predict sweet spots in tight reservoirs. Abstract : The hydrocarbon migration has significant effect on the maturity‐related parameters distribution such as 20S/(20S + 20R) and αββ/(αββ + α) for C29 steranes. Hydrocarbon expulsion enable Ts/(Ts + Tm) ratio in expelled oil much greater than that of retained oil at lower matural stage. The saturated hydrocarbon maturity biomarkers in retained oil and expelled oil vary in a subtly different pathways with increasing maturity, comparatively the aromatic hydrocarbon biomarkers, such as triaromatic steroids and methyl‐phenanthrene (MPI1 and MP2 ), regularly changed during maturation, which is not obviously affected by migration effects and can be used not only for thermal maturity predications but also for oil–oil or oil–source correlation.